Forging a New Frontier: Antimicrobial Peptides andNanotechnology Converging to Conquer GastrointestinalPathogens - Carnero Canales, Christian Shleider (2025)
Gastrointestinal infections, which are caused primarily by pathogenicbacteria, remain a signiﬁcant global health challenge. Their resilience isreinforced by various physical, biological, and biopharmaceutical barriers thatcomplicate conventional therapeutic strategies. This review delves into theintricate landscape of managing these infections, addressing microbiotaimbalances, the emergence of multidrug-resistant strains, and the impact ofdysbiosis and antibiotic overuse. Faced with these challenges, traditionaltherapies often fail, which is hindered by low bioavailability, prolongedregimens, and a growing risk of resistance. In this context, nanotechnologyapplied to antimicrobial peptides (AMPs) has emerged as a promisingsolution to enhance their stability and targeted delivery. Through a criticalapproach, diverse nanocarriers and their eﬃcacy against intestinal pathogensare evaluated both in vitro and in vivo. This review advocates for intensiﬁedresearch on the encapsulation and functionalization of AMPs, envisioningtheir potential to redeﬁne the control of intestinal infections on a global scale.